Speech-language pathology intervention in a youth justice setting: Benefits perceived by staff extend beyond communication. (4th July 2018) - Snow, Pamela C.; Bagley, Kerryn; White, Donna
Abstract: Purpose : Young people in youth justice (YJ) settings face high-risk for unidentified language disorder, however, speech-language pathology (SLP) services are not routinely offered in such settings. The aim of this study was to explore and describe the perceptions and experiences of YJ staff in a custodial centre of the utility of having a speech-language pathologist working with young offenders. Method : Following a SLP intervention trial, two staff focus groups were conducted by an independent SLP. Interview probes were developed through review of the literature and consultation with the practitioner who conducted the clinical intervention. Focus groups were digitally recorded for thematic analysis, which was carried out by the three authors independently. Result : YJ staff expressed consistently positive views about the SLP intervention trial in their centre. Staff indicated that they learnt a great deal about the complexity of communication difficulties in this population, and that this information informed and guided their own practices. They expressed surprise at the engagement of young people in the SLP service, and supported its embedding in the YJ setting. Conclusion : YJ staff endorsed the value of a SLP service in a custodial setting. Further research should focus on refining measurement of this service and its impact.